Analisis Hubungan Perputaran Persediaan dan Profitabilitas Rumah Makan Sakurakita Kota Palembang - Arradytia Permana; Randy Hidayat (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2020)
This study aims to determine how the relationship between inventory turnover and profitability at Sakurakita Restaurant. Data collection methods and types used are secondary data. Secondary data in the form of financial statements in the form of balance sheet and profit/loss reports from 2014 to 2019. The results of the study show that the higher the value of inventory turnover, it is not possible to increase profitability (Net Profit Margin)